Use of collaboration techniques and classification algorithms in personal healthcare - Trajkovik, Vladimir; Vlahu-Gjorgievska, Elena; Kulev, Igor (Springer-Verlag, 2012)
Adoption of mobile devices and technology in the field of medical monitoring and personal health care systems is very important nowadays, especially when it comes to certain categories of people with chronicle diseases who need 24 hour access to medical care. The collaborative Information system model we present in this paper, gives a new dimension in the usage of novel technologies in healthcare. Using mobile, web and broadband technologies enable the citizens to have ubiquity of support services where ever they may be. The model incorporates collaboration techniques and classification algorithms in order to generate recommendations and suggestions for preventive intervention. In addition, the system enables the patient (system user) to contact other people with similar condition and exchange their experience. This system improves the terms of home care treatment of the patient and allows the user to adapt his/ her physical activities to improve own health condition.
Keywords: Personal health care system . Social network . Collaborative techniques . Classification algorithms